Efficiency of organized teaching programme on knowledge regarding low glycaemic index diet among the diabetes mellitus patients admitted in selected hospitals at Bellary - Rani, Sigamala S. V. (International Journal of Contemporary Pediatrics, 2024)
Background: India leads the world with largest number of diabetic subjects earning the dubious distinction of being as “diabetic capital of world”. Diabetes is leading cause of death, disability and economic loss through the world. Prevalence of diabetes in the adults worldwide was estimated to be 4% in 1995 and is expected to be 5.4% by the year 2025. Methods: The study conceptual frame work based on Kings Goal attainment theory. The approach used for this study was evaluative one. Pre experimental study one group pretest and posttest design is used to collect the data. The independent variable of the study is organized teaching programme on knowledge regarding low glycaemic index diet among diabetes mellitus patients and dependent variable is knowledge on low glycaemic index diet in the management of diabetes mellitus patients the tool used to collect data was structured knowledge questionnaire. Results: The results of the study showed that the overall mean pretest knowledge of diabetes mellitus patients was 55.25% with the standard deviation of 2.77. The mean knowledge gain by the diabetes mellitus patients was 73.62% with the standard deviation of 1.89. The association was determined by using Pearson chi square test. The obtained "t" value 14.989 is greater than the table value at 0.01 level of significance. Therefore, "t" value is found to be significant. It means there is gain in knowledge level of diabetes mellitus patients. This supports that organized teaching programme on low glycaemic index diet is effective in increasing the knowledge level of diabetes mellitus patients. Conclusions: The present study attempted to assess effectiveness of organized teaching programme on knowledge regarding low glycaemic index diet among the diabetes mellitus patients admitted in selected hospitals at Bellary and concluded that there was a significant improvement in the knowledge after organized teaching programme. Thus, organized teaching programme is effective in improving the knowledge of the diabetes mellitus patients.